Praising the leader: personalist legitimation strategies and the deterioration of executive constraints. Issue 3 (3rd April 2023) - Brunkert, Lennart; von Soest, Christian
ABSTRACT : In the face of current democratic backsliding and autocratization processes, research has rediscovered issues of autocratic legitimation. However, the question of whether rulers' personalist rhetoric to bolster their legitimacy is followed by congruent political action remains underspecified. Using new expert-coded measures for 164 countries from the Varieties of Democracy project, we examine the political rhetoric–action link using using fixed effects models. The results confirm that shifts towards personalist legitimacy claims are no cheap talk but oftentimes important warning signals for a substantial deterioration of democratic quality, manifested in weaker judicial and legislative oversight of the executive branch. However, in contrast to much current concern, we show that liberal democracies seem to largely escape the negative repercussions of government discourses that increasingly stress the uniqueness of the ruler.